STIMULASI KEMAMPUAN ANAK TERHADAP KONSEP BILANGAN MELALUI MEDIA SAKU BILANGAN PADA TAMAN KANAK-KANAK ZULHIJJAH MEDAN - Mesran, Mesran; Pohan, Nurhikmah; Fadhilah, Cut Rafyqa; Khairani, Reni (Fakultas Agama Islam Universitas Al Washliyah, 2024)
This study aims to describe the stimulation of children's abilities towards the concept of numbers through number pocket media at Zulhijjah Kindergarten Medan and the development of children's abilities towards the concept of numbers at Zulhijjah Kindergarten Medan. The method used in this study is a qualitative method with data collection techniques used are observation, interviews, and documentation. The data analysis technique in this study was carried out by collecting data, summarizing data, presenting data and concluding. The results of the study indicate that Based on the results of research that has been conducted at Zulhijjah Kindergarten Medan regarding the stimulation of children's abilities towards the concept of numbers through number pocket media, it can be concluded that: 1) Stimulation of children's abilities in the concept of numbers is carried out with a well-structured learning plan design through learning planning and teaching modules that are adjusted to the theme and learning steps through interesting activities, namely playing while learning. 2) The development of children's abilities regarding the concept of numbers 1-30 through number pockets has developed as expected, such as children can name numbers 1-30, children can order numbers 1-30, children can pair numbers 1-30, children can connect numbers 1-30, children can write numbers 1-30.